Investing in agricultural water management to benefit smallholder farmers in Tanzania. AgWater Solutions Project country synthesis report. - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
This Working Paper summarizes research conducted as part of the AgWater Solutions Project in Tanzania between 2009 and 2012. The main findings of the project indicate that (1) pgrading community managed river diversion irrigation schemes leads to gains in water; (2) Access to surface water and groundwater resources through motorized pumps can raise yields, allow higher cropping intensities and diversification, and increase incomes. Investments to improve the ability of farmers to select, buy, rent and use motor pumps would enable them to grow high-value vegetables in the dry season. Farmers require training to select the right pumps for the job and to maintain them well. They may need affordable credit or pumps to rent; and (3) Farmers using conservation agriculture techniques have higher yields and see more environmental benefits, but it takes several years to recover the cost of the investment. The formation of farmer groups, training and demonstration from one farmer to another can enhance the spread of conservation agriculture techniques. productivity and household income. To maximize the livelihood benefits of communal irrigation schemes, investments should be made to improve infrastructure and to develop farmer skills in agronomic and irrigation practices and business skills. Micro-credit is a vital ingredient.